Administration of Zingiber zerumbet extract on performances and haematological parameters of broiler chickens. Issue 1 (April 2020) - Samadi, S; Wajizah, S; Tarman, A
Abstract: Due to the prohibition of antibiotics administration as feed additives in animal production, nutritionists need to develop strategies as replacement of antibiotics in animal feed. Phytogenic which is considered as replacement of antibiotic has been used widely in animal feed to promote growth and improve animal health. This experiment aimed to evaluate the use of Zingiber zerumbet extract on performance [BW, FI, and FCR] and hematological parameters of broiler chicken. A number of 100 mixed-sex broiler chickens were randomly allocated according to various treatment groups. Each treatment was administrated different levels of Z. zerumbet extract [P1=control, P2=0.025% of Z. zerumbet extract in the water, P3=0.050 % of Z. zerumbet extract in the water, and P4=0.025% of Z. zerumbet extract in the water]. Chickens were provided commercial feed with a nutrient requirement for started and growers. Water and feed were supplied ad libitum . Parameter observed in this experiment was broiler performance including BW, FI, and FCE each week up to 4 weeks and hematological parameter. One-way analysis of variance [ANOVA] was applied to determine the statistical difference by using SPSS. The significant differences between treatment were stated [P≤0.05]. The results of the experiment indicated that the use of Z. zerumbet in the water was not significantly different [P≥0.05] on chicken performance [BW, FI, and FCE]. Administration of Z. zerumbet extract in the water did not influence [P≥0.05] hematological parameters of broiler [hemoglobin, erythrosine, and thrombosis]. In conclusion, Z. zerumbet can be used as alternatives to feed additives to replace antibiotics in animal production.